2006
DOI: 10.1002/mas.20072
|View full text |Cite
|
Sign up to set email alerts
|

Processing and classification of protein mass spectra

Abstract: Among the many applications of mass spectrometry, biomarker pattern discovery from protein mass spectra has aroused considerable interest in the past few years. While research efforts have raised hopes of early and less invasive diagnosis, they have also brought to light the many issues to be tackled before mass-spectra-based proteomic patterns become routine clinical tools. Known issues cover the entire pipeline leading from sample collection through mass spectrometry analytics to biomarker pattern extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 179 publications
(255 reference statements)
0
141
0
2
Order By: Relevance
“…Previous work on SIMS data has demonstrated that binning is "the most effective technique to improve PCA performance" [17], in agreement with our preliminary experimental work (results not shown). Many variants of PCA or multivariate analyses have been reported for SIMS imaging mass spectrometry [11, 13, 18 -20], even applied to 3D distributions [21], and many other classification systems have been used in protein mass spectrometry [22]. The auto-alignment procedure benefits from PCA in noise reduction and the availability of more than onecomponent images for a more robust alignment and not classification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on SIMS data has demonstrated that binning is "the most effective technique to improve PCA performance" [17], in agreement with our preliminary experimental work (results not shown). Many variants of PCA or multivariate analyses have been reported for SIMS imaging mass spectrometry [11, 13, 18 -20], even applied to 3D distributions [21], and many other classification systems have been used in protein mass spectrometry [22]. The auto-alignment procedure benefits from PCA in noise reduction and the availability of more than onecomponent images for a more robust alignment and not classification.…”
Section: Discussionmentioning
confidence: 99%
“…by Hilario et al [8] Under this assumption, we can first process each mass spectrum independently over the mass dimension, for which peptide peaks are selected from the mass spectrum. In the next step, the selected peptides are assembled over the retention time (fractions) in order to study the elution profile in the LC dimension.…”
Section: Load New Fractionmentioning
confidence: 99%
“…To quantify the sensitivity of the COFRADIC methodology, i.e., the ability to detect low-abundant as well as high-abundant peptide peaks, we used the dynamic range expressed in decibels (dB), which was calculated as: 10 log 10 P max P min (8) with P max and P min denoting the maximum and minimum peptide abundance measured in an experiment, obtained via Eqn (5). A dynamic range of 37 dB was found for all COFRADIC replicates.…”
Section: Human Blood Samplementioning
confidence: 99%
“…As a result, pattern-based methods can achieve higher sample throughput than identity-based approaches, thereby enabling the analysis of larger numbers of patient samples for a given study. Furthermore pattern-based biomarker discovery usually utilizes powerful multivariate pattern recognition methods (23,24). However, identifying the peptides and proteins that constitute the pattern remains essential but is often difficult or impossible using these methods.…”
mentioning
confidence: 99%